POLEMIK KAIDAH KULLU ṢAḤABAH ‘UDÛL DAN KONTRIBUSI IBN ABÎ ḤÂTIM AL-RÂZÎ DI BIDANG ILMU JARḤ WA TA’DÎL - Imron, Ali (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
The discussion in this paper focuses on the contributions of Ibn AbÃ® HÃ¢tim al-Razi in the Jarh wa Ta'dil Science. This paper comes from library research. The method that used is descriptive-history-analysis. With this intellectual history approach, this paper finds that Ibn AbÃ® HÃ¢tim al-Razi's biggest contribution is seen in some basic theories of jarh wa ta'dil, ie the collective ta'dil which then develops into the theory of â€œkullu shahabah udulâ€ (all of the companions are fairness), objectification of the evaluation of the narrators of the hadith, and the rating of the narrators of the hadith, both in terms of jarh and ta'dil. Ibn Abi Hatim divided the ranks both on ta'dil or tajrih of hadiths narrators into four levels, those who doubt the critics of the hadith, the fair narrators, the strong history, the content of the report, the religion, the guardianship of the hadith, and the fearful, the truthful and the wizards, but sometimes mistaken, and Being honest and frank, but a lot of things go wrong.Keywordi: Ibn AbÃ® á¸¤Ã¢tim, Jará¸¥, Taâ€™dÃ®l, Hadis, â€˜UdÃ»l